Progress and Challenges of bioethics in Honduras. - Espinoza, Eleonora (Revista de Ciencias Forenses de Honduras, 2021)
Honduras does not have a national regulation on research ethics, which would allow it to establish a more fluid communication between the different actors involved in national research, standardize review procedures and ensure the safety of the participants in a more adequate manner. It is essential that the authorities of the Ministry of Health, as the governing body of health in the country, understand the importance of ethics and bioethics, a task that until now has been assumed by the academia through public and private universities. As an outstanding example, we cite the work done by the Bioethics Research Ethics Committee of the Faculty of Medical Sciences UNAH, which in recent years has promoted the creation of new committees and strengthened existing ones, promoted the formation of the network of research ethics committees in Honduras, and participation in a network of regional ethics committees in Central America and the Caribbean and recently promoted the creation of the National Bioethics Commission. It is undoubtedly important to work in national and international networks during emergency health situations such as the one we are currently experiencing with the COVID-19 pandemic. In this context, there have been a number of ethical dilemmas that have forced ethics committees to adopt changes in their review processes by being more flexible, such as shortening review times, increasing working hours of its members, as well as the implementation of online review tools.In order to consolidate the growth of bioethics as a fundamental pillar of science and research, it is necessary to have legislation that allows the governance of ethics and bioethics of research in the country, with the priority aim of guaranteeing the protection of the rights of research subjects.